Effect of oral vitamin E (α-tocopherol) supplementation on vascular endothelial function in Type 2 diabetes mellitus - Gazis, A.; White, D. J.; Page, S. R.; Cockcroft, J. R. (Diabetic medicine, 1999)
Summary Aims Vascular endothelial dysfunction, an early marker of atherosclerosis, has been demonstrated in Type 2 diabetes mellitus (DM). Vitamin E preserves endothelial function in animal models of diabetes and reduces cardiovascular risk. We examined endothelial function and the effect of vitamin E supplements in uncomplicated Type 2 DM. Methods Forty‐eight subjects with Type 2 DM and 21 controls had endothelial function assessed using forearm venous occlusion plethysmography with endothelium‐independent (sodium nitroprusside) and dependent (acetylcholine, bradykinin) vasodilators. Those with diabetes received 1600 iu daily oral α‐tocopherol or placebo, double‐blind for 8 weeks, and had endothelial function reassessed. Results The diabetic group had higher HbA1c (6.9 ± 1.4 vs 4.8 ± 0.6%; P < 0.01) and systolic (145 ± 15 vs 130 ± 16 mmHg; P < 0.01) but not diastolic blood pressure (79 ± 8 vs 76 ± 9 mmHg; P = 0.15). There was blunted vasodilation to acetylcholine (15 μg/min; P < 0.01) in subjects with diabetes. Vasodilation to sodium nitroprusside and bradykinin was similar (all P > 0.1). α‐tocopherol did not affect vasodilation to nitroprusside (P > 0.1), acetylcholine (P > 0.1) or bradykinin (P > 0.1). Conclusions There may be receptor‐specific endothelial dysfunction in subjects with uncomplicated Type 2 DM. This is not improved by treatment with α‐tocopherol. Diabet. Med. 16, 304–311 (1999)